“Hipercolesterolemia y su relación con la arteriosclerosis en pacientes de 50 a 70 años hospital Jaime Roldós aguilera Ventanas, provincia Los Ríos, septiembre 2017 a febrero 2018” - Macías Luna, Carmen Isabel (2018)
Atherosclerosis is a degenerative process of the blood vessels that begins with the deposition of lipoproteins and inflammatory cells in the arterial wall with the formation of fats (formed by macrophages full of lipids and foam cells) that progress to complex plaques (with a necrotic and lipidic center). fibrous outer layer); these plaques can break, releasing thrombi and showing the clinical symptoms of CVD. At the beginning and development of this atherosclerotic process are involved different risk factors that act synergistically, so that the cardiovascular risk derived from the simultaneous exposure to several of them is higher than expected by the sum of the risk of each of them separately . Being hypercholesterolemia one of the most important causes of heart disease and stroke is an unhealthy diet, physical inactivity, tobacco consumption and the harmful consumption of alcohol. The effects of behavioral risk factors can manifest in people in the form of high blood pressure, hyperglycemia, hyperlipidemia and overweight or obesity. These "intermediary risk factors," which can be measured in primary care centers, are indicators of an increased risk of heart attacks, strokes, heart failure and other complications. In the present study, 268 patients with a diagnosis of hypercholesterolemia are analyzed, where the highest incidence of the disease occurs in 58% in patients 50 to 60 years of age; especially in 61% of the male gender, this is due to 92% of that representative sample of family history of hypercholesterolemia, which was complemented by 74% of sedentary life and 91% of them consumed junk food. In this sense, this research determined that the basic need is the lack of knowledge on the part of the patients that were already analyzed and that the symptoms could be established as a consequence of the relationship between hypercholesterolemia and arteriosclerosis. Healthy and caring for the elderly.